SOCIODEMOGRAPHIC PROFILE OF YOUNG ADULTS IN THE CITY OF NOVO HAMBURGO, BRAZIL (Fiep Bulletin - online, 2012)
The objective of this study is to determine the profile of young adults aged 18 to 29 years who frequent any of the city facilities. The sample consists of young adults that responded a questionnaire with open and closed questions to describe their profile. Of the young adults interviewed, 60% were men and 91% work. The analysis of their weekly work load revealed that 65% work 40 hours a week, 26%, 30 hours a week, 3%, 20 h, and 6% have other work loads. Of all participants, 62.6% were studying at the time of the survey: 49.3% go to college and 6.7% have finished it; 18.6% finished high school, whereas 14.7% have not; 4% finished primary school, but 6.7% have not. Sports and leisure activities are practiced by 60% of the young adults, but the other 40% do not practice any of these activities. In the city of Novo Hamburgo, private organizations offer 65.8% of all activities, the municipal government, 17%, and the federal government, 4%. The number of hours during which young adults study and work make it difficult to practice physical activities because of the very little time left. Young adults in this city are workers that have little time for sports or leisure activities.
Keywords: young adults; sports and leisure; public policies